GERAKAN RESISTENSI PEMBANGUNAN NEW YOGYAKARTA INTERNATIONAL AIRPORT DI KECAMATAN TEMON KABUPATEN KULON PROGO, DIY - Prasetyo, Dhony Eko; Ali Azhar, Muhammad; Bandiyah, Bandiyah (Jurnal Nawala Politika, 2019)
ABSTRACT This study aims to determine the community resistance groups behind the construction of the New Yogyakarta International Airport, by answering the failure of resistance groups in rejecting the construction of new airports in Kulon Progo Regency. This study uses the theory of the New Social Movement with the concept approach of Political Opportunity Structure and the Framming Process (Snow & Benford). This study used descriptive qualitative method. Data collection techniques used were observation and in-depth interviews. This research shows that: First, the failure of the resistance group in the constuction of the New Yogyakarta International Airport due to the chairman of Wahana Tri Tunggal. Second, systemic deprivation carried out by the Yogyakarta government and the airport. Third, horizontal conflict caused the membership of the resistance group the fade. Key Words: New Social Movement-Resistance, Framing Media, Ecologic.